Modelling of hydrodynamic strain amplification in filled elastomers. Issue 1 (25th October 2016) - Darabi, Ehsan; Itskov, Mikhail; Klüppel, Manfred
Abstract: Polymer chains in filled elastomers are subject to a strain bigger than the overall (macro‐strain) applied to the specimen, which is described by a strain amplification factor. In the current paper, a micromechanical model for hydrodynamic strain amplification is presented. To this end, we develop the concept of the multiple filler fractions within the so‐called Dynamic Flocculation Model (DFM) framework. Accordingly, with increasing strain, a single unbroken virgin cluster gradually splits into smaller clusters. Thus, fractions of smaller filler clusters increase with the increasing strain, which in turn influences the filler‐induced hysteresis. The filler induced hysteresis is then described by the cyclic breakdown of the residual fragile filler clusters and re‐aggregation of the already broken filler‐filler bonds. The model includes a few number of physically motivated material constants describing the average filler cluster dimensions, filler‐filler and filler‐matrix interaction properties. (© 2016 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)